An efficient synthesis of cycloalkane-1, 3-dione-2-spirocyclopropanes from 1, 3-cycloalkanediones using (1-aryl-2-bromoethyl)-dimethylsulfonium bromides: application to a one-pot synthesis of tetrahydroindol-4(5H)-one. Issue 29 (15th July 2015) - Nambu, Hisanori; Fukumoto, Masahiro; Hirota, Wataru; Ono, Naoki; Yakura, Takayuki
Graphical abstract: Abstract: An efficient synthesis of cyclohexane- and cyclopentane-1, 3-dione-2-spirocyclopropanes from 1, 3-cycloalkanediones using sulfonium salts was achieved. The reaction of 1, 3-cycloalkanediones with (1-aryl-2-bromoethyl)-dimethylsulfonium bromides and powdered K2 CO3 in EtOAc provided the corresponding spirocyclopropanes in high yields. Furthermore, a one-pot synthesis of tetrahydroindol-4(5 H )-one from 1, 3-cyclohexanedione was achieved using the present protocol and a sequential ring-opening cyclization of spirocyclopropane with a primary amine.